THE LIFE QUALITY OF FAMILIES WITH A MEMBER WITH A MENTAL DISABILITY - Kozakova, Zdenka (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
This paper focuses on the quality of life of a family taking care of a mentally disabled member. In order to be able to provide families taking care of a disabled member with high-quality special-education care and support, it is at first necessary to learn about their needs in as complex a way as possible. This paper presents a selected summary of the results of a survey carried out by means of a questionnaire and a standardized questionnaire SEIQoL, in order to compare the quality of life of parents taking care of a mentally disabled child/children and the quality of life of parents taking care of a child/children without mental disability, and thus to ascertain those areas that would be desirable for further focus in the future.